The normative function of the usage of the prayer text of the “Lord's Prayer” in the historical-diachronic analysis of Germanic languages - Knychalska, Maja (Językowe, literackie i kulturowe refleksje na temat jedności w różnorodności, 2023)
The following article deals with the appropriateness of conducting research for historical-diachronic analysis on the basis of liturgical texts. The work is divided into three main parts. The introduction consists of a theoretical part in which the historical aspects of the research problem under consideration are presented. Subsequently, the author examines the individual, particularly striking similarities and differences manifested in the content of the oldest prayer of the Catholic faithful, the "Our Father", using the example of the texts of the Germanic family – English and German – differentiated according to the epoch of language development.Furthermore, the first and second consonant shifts (in relation to the title of the selected content itself), which played an important role in the formation of the Germanic languages, an analysis of the lyrical theme and its role in shaping the ecclesiastical sense of community, as well as the various grammatical aspects that run through the leading verses of the piece, are described.Using representation No. 5 as an example, the conflict of compatibility between liturgical language and vernacular language – in this case, modern German – is illustrated.In the concluding part of the paper, the author justifies the hypothesis that the attempt of a diachronic analysis based on the content of the sacred sphere is not a reliable source for linguistic research with the following arguments.